Questão social no Brasil à luz da teoria marxista da dependência : a crise da “nova república neoliberal” - Araújo, Ricardo Souza (2019)
This work aims to resume the fundamentals of the Marxist Theory of Dependence (TMD) to contribute to the understanding the expressions of the Social Issue in present-day Brazil. TMD consists on a cluster of Marxist thought dedicated to discussing, in the context of capital globalization, the particularities of the development of dependent economies, especially the Latin American ones. With the productive restructuring and counter-reform of the state operated over the last 30 years of the so-called Brazilian “New Republic”, the expressions of the Social Question exacerbate. This research relies on the materialist-dialectical method and the bibliographic research technique. We searched 90 articles from journals indexed in Social Work related to the theme. This study shows the urgent need to include TMD in the curriculum of undergraduate and postgraduate courses in Social Work in Brazil.The TMD, combined with the critical-dialectical tradition on Social Work, is a powerful instrument of analysis and intervention in the social reality in favor of the social rights of the working class.